Prediction of microalgae hydrothermal liquefaction products from feedstock biochemical composition1. Issue 6 (8th June 2015) - Leow, Shijie; Witter, John R.; Vardon, Derek R.; Sharma, Brajendra K.; Guest, Jeremy S.; Strathmann, Timothy J.
<x xml:space="preserve">Abstract</x> Models for microalgae hydrothermal liquefaction were developed from conversion of Nannochloropsis cultivated to varying biochemical composition and fatty acid content.